2020
DOI: 10.1177/0960327119867755
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine deficiency and oxidative stress induced by prolonged metronidazole therapy can explain its side effects of neurotoxicity and infertility in experimental animals: Effect of grapefruit co-therapy

Abstract: We aimed to explore the possible neurotoxicity and infertility mechanisms of prolonged metronidazole (MTZ) use and the effects of antioxidant grapefruit (GP) co-therapy on MTZ-induced complications. Sixty male albino Wistar rats were divided into four groups ( n = 15 each). Group I (control group) received 1% dimethyl sulfoxide (27 ml/ kg/day), group II (MTZ group) received MTZ (400 mg/kg/day), group III (MTZ + GP) received MTZ (400 mg/kg/ day) plus GP juice (27 ml/kg/ day) and group IV (GP group) received GP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In an experimental diabetic mellitus model, Sarandol et al (2020) discovered that plasma and tissue MDA levels decreased in the thiamine-administered group compared to the control group, while antioxidant indicators such as superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) increased. Another research on thiamine found that thiamine deficiency raises the risk of oxidative damage (Hassan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental diabetic mellitus model, Sarandol et al (2020) discovered that plasma and tissue MDA levels decreased in the thiamine-administered group compared to the control group, while antioxidant indicators such as superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) increased. Another research on thiamine found that thiamine deficiency raises the risk of oxidative damage (Hassan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The animals were starved overnight at the end of the experimental phase (2 weeks) and anaesthetized using diethyl ether inhalation; then, at the time of scarification, the blood samples were collected from the retro-orbital veins into plain tubes and centrifuged for 10 min at 1000 g and the separated sera were split into aliquots in 1 mL cryotubes and preserved at -80C until biochemical assays were carried out (Saleem et al, 2018;Hassan et al, 2020). The kidneys were dissected out immediately and cleaned of adhering tissues and were immersed in neutral buffered formalin10% for histopathology examination.…”
Section: Sample Collectionmentioning
confidence: 99%
“…17 In murine models, metronidazole toxicity was shown to be associated with oxidative stress and thiamine deficiency. 18 Thiamine deficiency or potentially its impaired metabolism would possibly explain the overlap of radiological features between Wernicke encephalopathy and metronidazole encephalopathy.…”
Section: Discussionmentioning
confidence: 99%